Avaliação Macroscópica e Morfométrica do Oviduto de Codornas (Coturnix coturnix japonica) Quando Alimentadas com Diferentes Níveis de Proteína - Artoni, SMB [UNESP]; Carneiro, APM [UNESP]; Giacomini, G [UNESP]; Moraes, VMB [UNESP]; Araújo, CSS [UNESP]; Araújo, LF [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2001)
Foram utilizadas doze codornas domésticas, divididas em três grupos de quatro aves cada. As aves receberam rações padronizadas contendo 16%, 20% e 24% de proteína, sendo alimentadas por um período de quinze semanas, quando foram pesadas e sacrificadas imediatamente. Após a abertura da cavidade abdominal e evisceração do trato gastrointestinal, os ovários e ovidutos foram dissecados e pesados. Com o auxílio de um paquímetro mediu-se o comprimento das partes do oviduto: infundíbulo, magno, istmo, útero e vagina e avaliou-se o número de pregas do magno e do istmo. Foram realizados cortes histológicos do magno, istmo e útero onde se obteve medidas das espessuras das camadas epitelial e glandular. Os dados foram submetidos a análise de variância (ANOVA) e observou-se que não houve diferenças significativas no peso corporal, peso do ovário, do oviduto e nos comprimentos das partes do oviduto bem como no número de pregas do magno e ístmo. Verificou-se diferenças significavas na espessura da camada epitelial do istmo de aves alimentadas com 20% de proteína na ração. Além disso, houve diferenças significativas na espessura da camada glandular do magno, istmo e útero das aves alimentadas com 24% de proteína na ração em relação às aves que receberam 16% e 20% de proteína. O nível de 24% de proteína aumentou a espessura da camada glandular do magno, ístmo e útero o que poderia resultar em melhoria no peso dos ovos e na espessura da casca.

The twelve domestic quail used in this study were divided into three groups, each with four birds. The groups received each a different treatment using standard feed containing three different levels of protein (16%, 20% and 24%). The treatments were continued for a period of fifteen weeks, after which the quails were immediately weighed and then killed. After opening the abdominal cavity and eviscerating the gastrointestinal tract, the ovaries and oviducts were dissected and weighed. Using a packymeter, the different parts of the oviducts were measured: infundibulum, magnum, isthmus, uterus and vagina. The number of folds present in the magnum and the isthmus were evaluated. Histologic sections of the magnum, isthmus and uterus were used to measure the thickness of their epithelial and glandular layers. The data obtained was statistically analysed using a Variance analysis (entirely casual distribution). It was concluded that there were no significative differences on body weight, ovary weigth, oviduct weigth and between the lengths of the different parts of the oviduct as well as regarding the number of folds in the magnum and the isthmus. It was concluded that there was significative differences were also found regarding the thickness of the epithelial layer of the isthmus in the birds treated with the feed containing 20% protein. Moreover there was a significative difference between the thickness of the glandular layer of the magnum, the isthmus and that of the uterus in the birds treated with 24% protein feed when compared to the quails that were given a 16% and 20% protein feed. Diet with 24% protein increased the glandular layer thickness of the magnum, isthmus and uterus that it could result in improvement in the weight of the eggs and in the shell quality.
Macroscopic and Morphometric Evaluation of Japanese Quail (Coturnix coturnix japonica) Oviduct When Fed Diets With Different Protein Levels
Keywords: Morphometry; oviduct; protein levels; quail; codornas; Morfometria; níveis de proteína; Oviduto